Qualitative Study: The Organizational Management for Academic Character Building of the AKBARA Polytechnic of Surakarta Member - Titis Wahyuono; Tri Wuryanto; Syarifah (STIE AAS Surakarta, 2020)
Various facts and phenomena of human moral degradation in higher education both lecturers, college students, and managers have occurred over time because of the rapid mordenization (Setiawati, 2012). Therefore, researchers are interested to know the qualitative study to find out how the social phenomenon in collage today so that it will bring up important points in the effort to create and build the character of college students. The approach used in this research is qualitative approach. The population in this study is the entire staff of AKBARA Surakarta Polytechnic. The sample in this study was 32 respondents using total sampling techniques. Research data is the main data by conducting interviews to all staff of AKBARA Surakarta Polytechnic. Then a scientific study was carried out from the source of the library which eventually obtained conclusions from problem solving about the research carried out. Data analysis techniques used are qualitative study research phenomena. The results showed that the characteristics of respondents as the highest sex in women was 51.5%, seen in terms of age in the age range 21-35 year olds with a percentage of 75%, and post-graduate education with a percentage of 48.5%. It is crucial to get a character education. This aims to strengthen morals and praiseworthy qualities for college students (in this case, college students) because intelligence in education is not enough without strong moral and character provisions. This is where the importance of character education. An attitude of empathy is one of the character qualities that can change the world. Polytechnic AKBARA concern about those activities in building the student's character. The management initiated the CAKRA Akbara, which consists of Competent, Toughness, and Character.